DEVELOPMENT OF AVIATION FRIENDLY DUSTBIN - BIN RAZALI, ABD RAZAK; BIN SULI, AZLIZUL; BIN ZAINAL, MOHAMMAD AZMIN (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2024)
This study underscores the critical importance of proper waste disposal, particularly through dustbin utilization, to mitigate Foreign Object Debris (FOD) risks in aviation. FOD poses significant threats to personnel and equipment safety, especially aircraft engines vulnerable to ingesting debris from maintenance and operational areas, potentially causing severe damage. The primary source of FOD originates from improperly managed waste in maintenance lines, including sharp objects and toxic substances, heightening risk within these critical zones. This research aims to advocate for effective waste disposal procedures to prevent FOD incidents, emphasizing meticulous dustbin usage as a primary method. The study employs a comprehensive review of literature and industry practices, alongside case studies, to analyze the impact of FOD on aviation safety. Key findings highlight the direct correlation between proper waste management and reduced FOD incidents, promoting safer and more efficient aircraft operations. Ultimately, implementing robust waste management strategies, including proactive dustbin use, is essential to mitigate FOD risks, ensuring enhanced safety and operational efficiency while protecting personnel and equipment in the aviation industry.